2016
DOI: 10.1093/jjco/hyw050
|View full text |Cite
|
Sign up to set email alerts
|

Residual tumor in cases of intermediate-risk neuroblastoma did not influence the prognosis

Abstract: Background: It remains unclear whether a residual tumor mass following therapy influences the prognosis of neuroblastoma. Methods: We retrospectively reviewed 20 patients with intermediate-risk tumors treated at our institution between 1993 and 2012 to elucidate whether additional treatment is required for residual tumors. Results: The patient ages at diagnosis ranged from 0 days to 7 years. The 5-year overall survival rate was 94.4%. Thirteen patients had Stage 3 disease and seven patients had Stage 4 disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Increasingly, subsets of patients with pNTs, including those with low‐ and intermediate‐risk NB with favorable clinical and biological characteristics (e.g., infants with small perinatal adrenal masses or those with favorable histology and absence of segmental aberrations) are observed based on frequent spontaneous regression or differentiation and excellent overall outcomes . There is also evidence to support that complete resection is not required for additional subsets of patients with low‐risk or intermediate‐risk NB with favorable biology . In addition, DeCarolis et al.…”
Section: Discussionsupporting
confidence: 84%
“…Increasingly, subsets of patients with pNTs, including those with low‐ and intermediate‐risk NB with favorable clinical and biological characteristics (e.g., infants with small perinatal adrenal masses or those with favorable histology and absence of segmental aberrations) are observed based on frequent spontaneous regression or differentiation and excellent overall outcomes . There is also evidence to support that complete resection is not required for additional subsets of patients with low‐risk or intermediate‐risk NB with favorable biology . In addition, DeCarolis et al.…”
Section: Discussionsupporting
confidence: 84%
“…In particular, the rare INSS4 intermediaterisk patients with persistent lesions following upfront chemotherapy may not require SCT based on our case series (including three intermediate risk) and other reports. [10][11][12][13] Furthermore, although patients with high-risk NB with residual lesions post induction have been shown to have an inferior outcome, these results may not extrapolate to residual lesions in these rare intermediate-risk "refractory" patients or high-risk patients with persistent lesions post SCT or immunotherapy. 8 Of the 11 patients in our analytic cohort who did not progress, eight of 11 were classified as high risk.…”
Section: Discussionmentioning
confidence: 99%
“…26 Iehara et al also reported that a residual mass at the end of treatment of NB did not influence the patients' prognoses in this study. 27 Therefore, invasive radical surgical resection and additional treatment, which will increase the severe complications or life-threatening conditions, may not be necessary.…”
Section: Discussionmentioning
confidence: 99%